Ionic liquid-assisted preparation of square-shaped Y2O3 nanoplates. (January 2015) - Wang, Lei; Fang, Hao; Xu, Hualan; Wang, Caoli; Li, Yuanjin; Liu, Yang; Zhong, Shengliang
Graphical abstract: Highlights: Y4 O(OH)9 (NO3 ) nanosheets were prepared by an ionic liquid-assisted mixed solvothermal route. Y2 O3 nanosheets were obtained after calcining the Y4 O(OH)9 (NO3 ) nanosheets. The Y2 O3 nanosheets are with length of about 300 nm and thickness of several nanometers. Abstract: Uniform square-shaped Y4 O(OH)9 (NO3 ) nanoplates with side length of about 300 nm and thickness of tens of nanometers have been successfully prepared by an ionic liquid-assisted mixed solvothermal route. Y2 O3 nanoplates with similar size were obtained after calcining the Y4 O(OH)9 (NO3 ) nanoplates at 800 °C. The products were analyzed by powder X-ray diffraction (XRD), thermogravimetric analysis (TG), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high resolution TEM (HRTEM), and electron diffraction (ED). The effects of reaction time, composition of solvents, and the molar ratio of reagents on the morphology of the products have been investigated. The possible formation mechanism of the Y4 O(OH)9 (NO3 ) nanoplates was also discussed. Y2 O3 :Eu 3+ nanoplates were also synthesized and their photoluminescent properties were examined.